Lectotypification of names of three species of Poa (Poaceae) and their morphological affinities - Bhadra, Ruma; Prasanna, P. V.; Naskar, Saikat (Phytotaxa, 2021)
Poa aitchisonii, P. falconeri and P. wardiana are lectotypified with nomenclatural notes. In absence of proper icons with analysis, worked out plant parts of two species from voucher specimens are provided as photoplates. Due to high degree of variability and in absence of concrete morphological features to distinguish species, morphological affinities of the three species with that of other close species are provided.